Answer with Step-by-step explanation:
We are given that
F=<0,-8>=0i-8j=-8j
![\theta=\frac{\pi}{3}](https://tex.z-dn.net/?f=%5Ctheta%3D%5Cfrac%7B%5Cpi%7D%7B3%7D)
The component of force is divided into two direction
1.Along the plane
2.Perpendicular to the plane
1.The vector parallel to the plane will be=![r=cos\frac{\pi}{3}i-sin\frac{\pi}{3}j=\frac{1}{2}i-\frac{\sqrt 3}{2}j](https://tex.z-dn.net/?f=r%3Dcos%5Cfrac%7B%5Cpi%7D%7B3%7Di-sin%5Cfrac%7B%5Cpi%7D%7B3%7Dj%3D%5Cfrac%7B1%7D%7B2%7Di-%5Cfrac%7B%5Csqrt%203%7D%7B2%7Dj)
By using ![cos\frac{\pi}{3}=\frac{1}{2},sin\frac{\pi}{3}=\frac{\sqrt 3}{2}](https://tex.z-dn.net/?f=%20cos%5Cfrac%7B%5Cpi%7D%7B3%7D%3D%5Cfrac%7B1%7D%7B2%7D%2Csin%5Cfrac%7B%5Cpi%7D%7B3%7D%3D%5Cfrac%7B%5Csqrt%203%7D%7B2%7D)
Force along the plane will be=![\mid F_x\mid=F\cdot r](https://tex.z-dn.net/?f=%5Cmid%20F_x%5Cmid%3DF%5Ccdot%20r)
Force along the plane will be =
N
By using ![i\cdot i=j\cdoty j=k\cdot k=1,i\cdot j=j\cdot k=k\cdot i=j\cdot i=k\cdot j=i\cdot k=0](https://tex.z-dn.net/?f=i%5Ccdot%20i%3Dj%5Ccdoty%20j%3Dk%5Ccdot%20k%3D1%2Ci%5Ccdot%20j%3Dj%5Ccdot%20k%3Dk%5Ccdot%20i%3Dj%5Ccdot%20i%3Dk%5Ccdot%20j%3Di%5Ccdot%20k%3D0)
Therefore, force along the plane=![\mid F_x\mid(\frac{1}{2}i-\frac{\sqrt 3}{2}j)=4\sqrt 3(\frac{1}{2}i-\frac{\sqrt 3}{2}j)](https://tex.z-dn.net/?f=%5Cmid%20F_x%5Cmid%28%5Cfrac%7B1%7D%7B2%7Di-%5Cfrac%7B%5Csqrt%203%7D%7B2%7Dj%29%3D4%5Csqrt%203%28%5Cfrac%7B1%7D%7B2%7Di-%5Cfrac%7B%5Csqrt%203%7D%7B2%7Dj%29)
2.The vector perpendicular to the plane=![r=-sin\frac{\pi}{3}-cos\frac{\pi}{3}=-\frac{\sqrt 3}{2}i-\frac{1}{2}j](https://tex.z-dn.net/?f=r%3D-sin%5Cfrac%7B%5Cpi%7D%7B3%7D-cos%5Cfrac%7B%5Cpi%7D%7B3%7D%3D-%5Cfrac%7B%5Csqrt%203%7D%7B2%7Di-%5Cfrac%7B1%7D%7B2%7Dj)
The force perpendicular to the plane=![\mid F_y\mid=F\cdot r=-8j(-\frac{\sqrt 3}{2}i-\frac{1}{2}j)](https://tex.z-dn.net/?f=%5Cmid%20F_y%5Cmid%3DF%5Ccdot%20r%3D-8j%28-%5Cfrac%7B%5Csqrt%203%7D%7B2%7Di-%5Cfrac%7B1%7D%7B2%7Dj%29)
The force perpendicular to the plane=
N
Therefore, ![F_y=4(-\frac{\sqrt 3}{2}i-\frac{1}{2}j)](https://tex.z-dn.net/?f=F_y%3D4%28-%5Cfrac%7B%5Csqrt%203%7D%7B2%7Di-%5Cfrac%7B1%7D%7B2%7Dj%29)
Sum of two component of force=![F_x+F_y=4\sqrt 3(\frac{1}{2}i-\frac{\sqrt 3}{2}j)+4(-\frac{\sqrt 3}{2}i-\frac{1}{2}j)](https://tex.z-dn.net/?f=F_x%2BF_y%3D4%5Csqrt%203%28%5Cfrac%7B1%7D%7B2%7Di-%5Cfrac%7B%5Csqrt%203%7D%7B2%7Dj%29%2B4%28-%5Cfrac%7B%5Csqrt%203%7D%7B2%7Di-%5Cfrac%7B1%7D%7B2%7Dj%29)
Sum of two component of force=![2\sqrt 3i-6j-2\sqrt3 i-2j=-8j](https://tex.z-dn.net/?f=2%5Csqrt%203i-6j-2%5Csqrt3%20i-2j%3D-8j)
Hence,sum of two component of forces=Total force.